Efficacy of Topical Mesenchymal Stem Cell Therapy in the Treatment of Experimental Dry Eye Syndrome Model - Emrullah Beyazyıldız; Ferda Alpaslan Pınarlı; Özlem Beyazyıldız; Emine Rümeysa Hekimoğlu; Uğur Acar; Muhammed Necati Demir; Aynur Albayrak; Figen Kaymaz; Güngör Sobacı; Tuncay Delibaşı (Stem Cells International)
Purpose. The current study was set out to address the therapeutic efficacy of topically applied mesenchymal stem cells (MSCs) on dry eye syndrome (DES) induced by benzalkonium chloride (BAC) in rats. Methods. Rats were divided into two groups just after establishment of DES. Eye drops containing either bromodeoxyuridine labeled MSCs (n=9) or phosphate buffer solution (n=7) were topically applied once daily for one week. Schirmer test, break-up time score, ocular surface evaluation tests, and corneal inflammatory index scoring tests were applied to all rats at baseline and after treatment. All rats were sacrificed after one week for histological and electron microscopic analysis. Results. Mean aqueous tear volume and tear film stability were significantly increased in rats treated with MSCs (P<0.05). Infiltration of bromodeoxyuridine labeled MSCs into the meibomian glands and conjunctival epithelium was observed in MSCs treated rats. Increased number of secretory granules and number of goblet cells were observed in MSCs treated rats. Conclusion. Topical application of MSCs could be a safe and effective method for the treatment of DES and could potentially be used for further clinical research studies.